Analisis Perkembangan Karakter Tanggung Jawab Peserta Didik Dalam Penggunaan Gadget di Kelas V SDN Bangsri 01 - Malikhatun Chasanah; Diah Sunarsih; Laelia Nurpratiwiningsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
Character education is a place that must be owned by human children so that human children become human beings who have morals in character socialization. Every human being has a different character, there are several kinds of character, namely responsibility. Responsibility is an educational activity in building human resources carried out by humans to educate and have a noble character for students. This study aims to describe the development of the character of the responsibility of students in completing homework assignments using gadgets, and to mention the factors that can affect the use of gadgets in completing homework assignments given the importance of developing the character of responsibility of students in doing homework assignments to measure how well students understand. students understand the learning that has been taught by the teacher, so that the teacher can provide an evaluation at the time of learning which will be continued in the next lesson. The method used in this research is by using qualitative descriptive. The data analysis technique used in this study is to use internal data collection with sources from interviews, observations and documentation. The object of the resource persons are students of class V, teachers of class V, parents of class V students. The results of research on the development of the character of responsibility for using gadgets in completing homework assignments are that students can be responsible for understanding homework assignments by using gadgets so that they get good grades. quite satisfactory, then students can overcome obstacles when there are obstacles in completing assignments, and students can also collect assignments and on time. The factors that can affect the development of students' homework assignments are gender factors, namely between male students and female students in collecting assignments, social factors which refer to working on students' assignments in groups, then parents who always accompany students in the work. PR assignment.